(untitled) (Scientific journal of the Fergana State University, 2026)
This paper examines coevolutionary features of the tri‑trophic plant–phytophage–entomophage system in vegetable agroecosystems. Using 2012–2025 data (227 species: 155 phytophages, 72 entomophages), we show resource centralization around Solanaceae, phenological matching, and during invasions a ‘generalism → re‑specialization’ sequence. We propose FMI–H2’–Q as an integrative indicator linking network modularity and tri‑trophic stability.